1966
DOI: 10.1126/science.151.3712.817
|View full text |Cite
|
Sign up to set email alerts
|

Rubidium-Strontium Age of the Bosumtwi Crater Area, Ghana, Compared with the Age of the Ivory Coast Tektites

Abstract: Rocks from the vicinity of Bosumtwi crater, Ghana, and a repre-sentative collection of Ivory Coast tektites have been analyzed mass spectrometrically for rubidium, strontium, and strontium isotopic composition. The data from the rocks of the crater area yield an age of 1.97 x 10(9) years (lambda(gb) = 1.47 chi 10(-11) year(-1)). The data for the Ivory Coast tektites fall on this isochron. This identity of age values for the Ivory Coast tektites and the Birrimian basement rocks of West Africa strongly supports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

1966
1966
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…The geographical distribution of microtektite-bearing deep-sea cores was used to determine the extent of the strewn field Glass et al , 1991. A variety of arguments supported the conclusion that Bosumtwi was most likely this source crater, including similar chemical compositions (Schnetzler et al 1967;Jones 1985), similar isotopic characteristics for the tektites and rocks found at the crater (e.g., Schnetzler et al 1966;Lippolt and Wasserburg 1966;Shaw and Wasserburg 1982), and the similar ages of tektites and Bosumtwi impact glasses (e.g., Gentner et al 1964Gentner et al , 1967. Koeberl et al (1998) found that the oxygen isotopic composition of the country rocks (δ 18 O = 11.3-13.6‰) and those of the tektites (δ 18 O = 11.7-12.9‰) agree fairly well, and showed that in a 87 Sr/ 86 Sr versus 1/Sr plot, as well as in an ε Sr versus ε Nd diagram, the tektites plot within the field defined by the metasedimentary and granitic Bosumtwi country rocks.…”
Section: Brief Summary Of the Geology Of Bosumtwimentioning
confidence: 99%
“…The geographical distribution of microtektite-bearing deep-sea cores was used to determine the extent of the strewn field Glass et al , 1991. A variety of arguments supported the conclusion that Bosumtwi was most likely this source crater, including similar chemical compositions (Schnetzler et al 1967;Jones 1985), similar isotopic characteristics for the tektites and rocks found at the crater (e.g., Schnetzler et al 1966;Lippolt and Wasserburg 1966;Shaw and Wasserburg 1982), and the similar ages of tektites and Bosumtwi impact glasses (e.g., Gentner et al 1964Gentner et al , 1967. Koeberl et al (1998) found that the oxygen isotopic composition of the country rocks (δ 18 O = 11.3-13.6‰) and those of the tektites (δ 18 O = 11.7-12.9‰) agree fairly well, and showed that in a 87 Sr/ 86 Sr versus 1/Sr plot, as well as in an ε Sr versus ε Nd diagram, the tektites plot within the field defined by the metasedimentary and granitic Bosumtwi country rocks.…”
Section: Brief Summary Of the Geology Of Bosumtwimentioning
confidence: 99%
“…Early work describing the formation of the Bosumtwi structure proposed both cryptoexplosive (Rohleder 1936;Junner 1937) and meteorite impact (MacLaren 1931) mechanisms for its origin. A large body of subsequent geological, geophysical, and geochemical work has clearly demonstrated its impact origin (e.g., Littler et al 1961;El Goresy 1966;Lippolt and Wasserburg 1966;Schnetzler et al 1966Schnetzler et al , 1967Kolbe et al 1967;Chao 1968;Jones et al 1981;Jones 1985aJones , 1985bKoeberl et al 1998;Reimold et al 1998;Plado et al 2000;Boamah and Koeberl 2002Scholz et al 2002;Wagner et al 2002;Pesonen et al 2003;Artemieva et al 2004;Dai et al 2005; multiple sources in this issue).…”
Section: Introductionmentioning
confidence: 99%
“…1) (Barnes 1961;Lippolt and Wasserburg 1966;Schnetzler et al 1966Schnetzler et al , 1967Glass 1969;Durrani and Khan 1971;Glass and Zwart 1979;Jones 1985a;Koeberl et al 1996aKoeberl et al , 1997Koeberl et al , 1998Dai et al 2005). Remote sensing, geophysical, and drill core studies demonstrate that the Bosumtwi crater, which is buried beneath up to 294 m of post-impact lacustrine sediments, is a complex impact structure characterized by an annular moat filled with over 135 m of lithic and suevitic impact breccia and by a 130 m high, 1.9 km wide, faulted central uplift overlain by about 25 m of melt-bearing impact-related units ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Once thought of as a volcanic caldera (Junner 1937), a number of geochemical tests and the presence of planar deformation features (e.g., Koeberl 1994b; Koeberl and Reimold 2005;Schnetzler et al 1966Schnetzler et al , 1967 have confirmed that the crater is an impact structure. The crater has a complex form with a slightly pronounced outer ring 20 km in diameter surrounding the crater rim, which is 10.5 km in diameter, and with a central uplift 1.5 km in diameter .…”
Section: Introductionmentioning
confidence: 99%